2006
DOI: 10.2224/sbp.2006.34.3.319
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Social Stereotypes With the Photo Projective Method

Abstract: This study aimed to measure social stereotypes with the Photo Projective Method (PPM) developed by Noda (1988). PPM is a new technique based on a projective method to capture perceived environments by photographs. Ten university students were provided with cameras and requested to take three pictures of “something representative of our university” and three pictures of “something not representative of our university.” The results showed that stereotypes were measured on a microlevel and macrolevel by PPM. Als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Wang and Redwood-Jones (2001) note that the participants' "familiarity with their surroundings gives community members a distinct advantage over professionals in their ability to move through the community, [and to] portray its strengths and concerns" visually. The purpose is to assess a community from the perspective of members; to communicate participant views to policy makers (Wang & Redwood-Jones, 2001); the photo-projective method attempts to "understand the individual's internal mental world" based on their reflection and relationship with the external context illustrated in their photographs (Okamoto et al, 2006); to highlight and neutralize power and agency imbalances in research and policy (Wang & Burris, 1997). …”
Section: 22mentioning
confidence: 99%
“…Wang and Redwood-Jones (2001) note that the participants' "familiarity with their surroundings gives community members a distinct advantage over professionals in their ability to move through the community, [and to] portray its strengths and concerns" visually. The purpose is to assess a community from the perspective of members; to communicate participant views to policy makers (Wang & Redwood-Jones, 2001); the photo-projective method attempts to "understand the individual's internal mental world" based on their reflection and relationship with the external context illustrated in their photographs (Okamoto et al, 2006); to highlight and neutralize power and agency imbalances in research and policy (Wang & Burris, 1997). …”
Section: 22mentioning
confidence: 99%
“…On the other hand, it is known that subconscious discriminations, measured through implicit behavioral tendencies towards specific targets, exist independently of conscious reports. The photo projective method used in the present study and the implicit association test (IAT) used in social psychology are considered to be powerful tools for measuring unconscious attitudes towards objects (Mahidin & Maulan, 2012;Matsui, 2020;McConnell & Leibold, 2001;Okamoto et al, 2006). For example, a previous study reported that IAT can assess individual differences in implicitly measured selfconcepts of personality that are not accessible through traditional explicit self-ratings (Asendorpf et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the owner's impression evaluation, the agent's social presence was measured by a measurement similar to the "photo projective method" (Mahidin & Maulan, 2012;Matsui, 2020;Okamoto et al, 2006), which was expected to reflect the owner's subconscious toward the agent from photographs taken by the agent's (stuffed animal's) owner. By measuring the influence of the existence of a virtual social network on the social presence of stuffed animals from multiple perspectives, we aimed to investigate whether the proposed method can increase social presence towards the agent at an unconscious level.…”
Section: Introductionmentioning
confidence: 99%
“…Serfass and Sherman [ 50 ] analyzed the TAT situation perception, the results of which supported a two-component view including an objective component that could be attributed to perception conditions and a subjective component that could be attributed to the subject. Okamoto et al [ 36 ] employed the projective PPM images to measure stereotypes and described the results as acceptable and objective. Leite et al [ 31 ] assessed the pictorial test of cognitive profiles (TPPC) and proved the results reliable.…”
Section: Introductionmentioning
confidence: 99%